2017
DOI: 10.3389/fmicb.2017.00556
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome-Based Amplified Fragment Length Polymorphism Analysis Reveals Genetic Diversity in Candida africana

Abstract: This study aimed at investigating the genetic diversity of a panel of Candida africana strains recovered from vaginal samples in different countries. All fungal strains were heterozygous at the mating-type-like locus and belonged to the genotype A of Candida albicans. Moreover, all examined C. africana strains lack N-acetylglucosamine assimilation and sequence analysis of the HXK1 gene showed a distinctive polymorphism that impair the utilization of this amino sugar in this yeast. Multi-locus sequencing of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(78 reference statements)
4
15
0
Order By: Relevance
“…Candida africana shows a global distribution and mainly causes genital infections [7]. Review of C. africana in literature has been summarized in Additonal file 5: Table S5 and displayed as a world map in Additonal file 10: Figure S5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida africana shows a global distribution and mainly causes genital infections [7]. Review of C. africana in literature has been summarized in Additonal file 5: Table S5 and displayed as a world map in Additonal file 10: Figure S5.…”
Section: Discussionmentioning
confidence: 99%
“…Candida africana represents the phenotypic variation occurring in C. albicans [5]. Candida africana colonized mainly in human genitalia and cause vaginal infections [6, 7]. Its distribution appears to be worldwide [512].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are Saccharomyces eubayanus / S. uvarum ( 101 ), Candida albicans / C. africana/C. stellatoidea ( 102 106 ), Candida auris / C. haemulonii/C. duobushaemulonii ( 107 112 ), Candida glabrata / C. nivariensis / C. bracarensis ( 103 , 113 115 ), Candida parapsilosis / C. orthopsilosis / C. metapsilosis ( 103 , 116 ), Malassezia furfur that now comprises 16 species ( 117 119 ), Trichosporon cutaneum with at least 10 species ( 120 , 121 ), the Aspergillus fumigatus complex ( 122 124 ), Coccidioides immitis / C. posadasii ( 100 ), and Paracoccidioides brasiliensis/P.…”
Section: Perspectivementioning
confidence: 99%
“…Our results revealed that GlcNAc was only able to inhibit C. tropicalis filamentation following its NGT1-mediated internalization. Candida species can utilize GlcNAc as a carbon source through a catabolic mechanism dependent upon HXK1, DAC1, and NAG1 [34,43,48]. We found that the expression of NGT1, HXK1, DAC1, and NAG1 were all significantly elevated in cells grown on GlcNAc-containing media relative to those grown on glucose-containing media.…”
Section: Discussionmentioning
confidence: 77%